2008
DOI: 10.1016/j.neuroimage.2008.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Network activation during bimanual movements in humans

Abstract: The coordination of movement between the upper limbs is a function highly distributed across the animal kingdom. How the central nervous system generates such bilateral, synchronous movements, and how this differs from the generation of unilateral movements, remains uncertain. Electrophysiologic and functional imaging studies support that the activity of many brain regions during bimanual and unimanual movement are quite similar. Thus, the same brain regions (and indeed the same neurons) respond similarly duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
74
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(83 citation statements)
references
References 131 publications
7
74
2
Order By: Relevance
“…Mirror movements could be due to abnormal spread of the motor plan to both M1 regions, either from a single motor planning area or from independent planning centers located in each hemisphere. More specifically, since the dominant hemisphere appears to initiate activity responsible for synchronous bimanual movement [86], it is possible that the dominant hemisphere is responsible for MM during intended independent bimanual tasks because of an interhemispheric miscommunication due to abnormal transcallosal connections (Fig. 1).…”
Section: Abnormal Motor Planningmentioning
confidence: 99%
See 1 more Smart Citation
“…Mirror movements could be due to abnormal spread of the motor plan to both M1 regions, either from a single motor planning area or from independent planning centers located in each hemisphere. More specifically, since the dominant hemisphere appears to initiate activity responsible for synchronous bimanual movement [86], it is possible that the dominant hemisphere is responsible for MM during intended independent bimanual tasks because of an interhemispheric miscommunication due to abnormal transcallosal connections (Fig. 1).…”
Section: Abnormal Motor Planningmentioning
confidence: 99%
“…Dissociation of the motor output arising from each hemisphere also requires appropriate inhibition of the motor cortex ipsilateral to the voluntary movement, through inhibitory transcallosal projections. During complex bimanual movements, the dominant hemisphere should play a modulatory role in finding a good balance with the other hemisphere to ensure the coordination of action plans and the dissociation of motor outputs [86]. Dysfunction or morphological alterations of the multiple neural circuits underlying bimanual control may result in involuntary MM (Fig.…”
Section: Abnormal Motor Planningmentioning
confidence: 99%
“…This view has been challenged by evidence in monkeys that showed a subset of neurons within the primary motor cortex (M1) specifically engaged in the control of bimanual movements (Donchin et al, 1998;Gribova et al, 2002). Several neuroimaging studies in humans have demonstrated that anti-phase and in-phase movements share a large core motor network, but additional activations in bihemispheric motor networks have also been detected during anti-phase activities (Sadato et al, 1997;Ehrsson et al, 2002;Ullen et al, 2003;Rocca et al, 2007;Walsh et al, 2008;Meister et al, 2010). In previous studies using functional magnetic resonance imaging (fMRI), brain activity related to transitions from anti-phase to in-phase has been reported to occur in right-lateralized prefrontal, SMA, dorsal premotor (PMd), parietal regions and cerebellum (MeyerLindenberg et al, 2002;Aramaki et al, 2006b).…”
Section: Introductionmentioning
confidence: 99%
“…For example, bimanual coupling necessary for the maintenance of stable relative phase patterns appears to require simultaneous activity of several cortical areas, some of which may also be engaged in purely unimanual tasks (Kazennikov et al, 1999;Debaere et al, 2001;Cardoso de Oliveira, 2002;Nair et al, 2003;Koeneke et al, 2004;Aramaki et al, 2006a,b;Daffertshofer et al, 2005;Serrien, 2008;Walsh et al, 2008). Primary motor cortices (M1), supplementary motor areas (SMA), dorsal premotor cortex, cingulate motor area (CMA), primary somatosensory cortices (S1), superior parietal lobule (PAR), posterior parietal cortex (PP) have all been shown to play a contributory role.…”
Section: Introductionmentioning
confidence: 99%